Ship emissions accounting in the port of Singapore – a preliminary analysis on the crude oil tanker segment - Tan, Lovine Nin (Nanyang Technological University, 2022)
The purpose of this paper is to conduct emission accounting for the crude oil tanker in the port of Singapore. It is a preliminary analysis to understand some of the emission patterns generated by this shipping segment. This is completed by using a bottom-up approach using Automatic Identification System data collected in the port. Singapore is a vital maritime hub and one of the world's most important ports. She has been named the world's leading maritime city for several years in a row, and she was recently crowned again in 2022. Singapore's port's key strengths are that it is a transhipment and bunkering hub, as well as a key location for related maritime services.